Challenges for Islamic Education Teachers in the Era of Society 5.0: Between Technology and Spirituality - Sudirman Sudirman; Adawiyah Pettalongi; Ubadah Ubadah (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This paper examines the challenges faced by Islamic Religious Education (PAI) teachers in integrating technology and spiritual values in the Society 5.0 era. With the rapid development of technologies such as artificial intelligence and the Internet of Things, PAI teachers are required to not only teach religious knowledge but also equip students with ethical and spiritual understanding in the use of technology. This study uses a qualitative approach with a phenomenological method, involving interviews and observations to identify challenges and strategies that can be used by PAI teachers. The results show that the main challenges include a lack of technology training, difficulties in integrating spiritual values, and limited resources. On the other hand, technology also offers opportunities to improve PAI teaching through interactive digital platforms. Therefore, it is important for teachers to adapt and develop relevant teaching methods. Recommendations include professional training for teachers, integration of technology in the curriculum, and collaboration between schools, parents, and the community to support students' spiritual development. Thus, PAI education is expected to produce a generation that is balanced between knowledge and spiritual values of Society 5.0, Islamic Religious Education, Technology, Spirituality, Teachers.